Assessing Pesticide Sales Trends: An Agrovet Survey in Parasi, Rupandehi and Kapilvastu Districts of Lumbini Province - Panthi, Shrijana; Nyaupane, Sushil (Far Western Review, 2025)
Study assesses practices related to the sale of pesticides and safety measures, the provision of licenses and training for pesticide retailers, and the status of the most traded pesticides in the Parasi, Rupandehi, and Kapilvastu districts. 69 agrovet respondents were selected through a simple random sampling method in the regions. Insecticides were found to be the most demanded type of pesticide (79.7%), followed by fungicides (20.3%). Among the available insecticides, the combination of Chlorpyriphos 50% + Cypermethrin 5% EC was the most traded with index value 0.85. For fungicides, mancozeb was the top choice, followed by the herbicide ammonium salt glyphosate, while aluminum phosphide was the most favored rodenticide. During the study, lack of policies for the proper disposal of expired pesticides was observed. Additionally, there was a low percentage (38.2%) of personal protective equipment (PPE) sales, indicating farmers’ minimal attention to pesticide exposure safety. The survey also revealed challenges faced by retailers, including issues such as open borders, the rising number of agrovets in local areas, difficulties in convincing farmers to adopt safety measures, and a lack of pesticide knowledge among farmers. This suggests that the government should ensure stricter monitoring and more rigorous enforcement of regulations regarding the sales of pesticides.